KAJIAN STRUKTUR SRPMM PADA GEDUNG RKB SDN 027 SAMARINDA DENGAN MENGGUNAKAN FLAT SLAB - SETIAWAN, MICHAEL JELLY (KURVA S JURNAL MAHASISWA, 2018)
Currently, the development of science and technology globally rapidly and quickly. One of the real actions undertaken by the Government of the city of Samarinda in improving the quality of education is to do a development infrastructure Building New Classrooms SDN 027 Samarinda. The building of new Classrooms build with reinforced concrete structure of the ordinary or conventional systems, which at the end of this task the author will do a SRPMM structure studies Building RKB SDN 027 Samarinda using flat slab. By using flat slab will be obtained some advantages like flexibility toward spatial, time work a relatively shorter, simplicity in installation of Mechanical Electrical and Plumbing (MEP), the save height space, high the room is bigger and more.On the planning of this building was modified into 6 floors of which previously only 2 floors only.Â The building will be modelled in 3D and burdened by gravity and seismic loads.Â The planned building must meet the criteria of drift and the Byway are permitted in order to meet the safety aspects on the building.The results of the design obtained slab thickness of 180 mm, 100 mm thick drop panel with a width of 120 cm either towards the x-axis and towards the y-axis, and with the use of a column with dimensions of 600 mm x 600 mm. Shear wall is designed with a thickness of 250 mm by using a reinforcedment concrete. From the dynamic analysis showed that the structure of the building is eligible drift with a period (T) of 1.788 seconds.